KOMPOSISI IKAN PETEK (LEIOGNATHIDAE) DI PERAIRAN BARAT SUMATRA [Composition of pony fish (Leiognathidae) in west of Sumatra waters] - Wedjatmiko Wedjatmiko (Jurnal Iktiologi Indonesia, 2007)
The research was conducted on August, 2005 and August, 2006 using RV. Bawal Putih. Result of this research shows that Pony fish (Leiognathidaej was the largest family catched 59.85 % (2005) and 49.74 % (2006). There was three genera of Leiognathidae catched in West of Sumatra waters namely Leiognathus (10 species), Secutor (2 species) and Gaza (1 species). The highest catch of the pony fish was a Leiognathus bindus 59.85% (2005) and 49.74% (2006), (by average size 8.0 - 8.5 cm (FL)). The largest size of pony fish in west of Sumatra waters was a Leiognathus fasciatus (with average size 18.0 cm (FL) and range size 13.0 - 20.5 cm). Vertically distribution of Leiognatidae was in the waters 41 - 50 m in depth, especially for Leiognathus bindus.